A study on the perception towards integrity among employees in three district councils / Mohd Noor Hidayat Jimainal and Mohd Saiful Adzhari - Jimainal, Mohd Noor Hidayat; Adzhari, Mohd Saiful (2012)
This study was conducted to identify the perception of integrity among the employees of district council and the relationship between the perceptions of integrity with the factors that associate with it. The samples of 100 respondents from Tuaran District Council, Penampang District Council and Putatan District Council were selected randomly to answer the questionnaire in this research. The results of this study identified that majority of the employees having a high perception towards integrity. Apart from that, the findings also show that only employees working environment have a correlation with their perception towards integrity.